2014
DOI: 10.1121/1.4870490
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanisms underlying voluntary responses to pitch-shifted auditory feedback

Abstract: Previous research has shown that vocal errors can be simulated using a pitch perturbation technique. Two types of responses are observed when subjects are asked to ignore changes in pitch during a steady vowel production, a compensatory response countering the direction of the perceived change in pitch and a following response in the same direction as the pitch perturbation. The present study investigated the nature of these responses by asking subjects to volitionally change their voice fundamental frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…The results show a consistent tendency: the deeper the F0 modulation the larger the vocal response in F0, being consistent with previous TAF studies [9][10][11]. Figure 4 shows two representative data for averaged F0 response curves obtained from all the male and female speakers.…”
Section: F0 Response Curvessupporting
confidence: 88%
“…The results show a consistent tendency: the deeper the F0 modulation the larger the vocal response in F0, being consistent with previous TAF studies [9][10][11]. Figure 4 shows two representative data for averaged F0 response curves obtained from all the male and female speakers.…”
Section: F0 Response Curvessupporting
confidence: 88%
“…This aspect of our finding is complementary to one recent behavioral study showing that vocal responses observed when vocally-untrained participants were instructed to ignore PSS did not differ from those observed when they were instructed to compensate for PSS that required a focusing attention on the PSS direction 16 , suggesting that vocal compensation for pitch perturbations cannot be consciously modulated. It is also noted from other findings that vocally-untrained participants generally produce compensatory responses to PSS even when told to ignore them 5 14 15 , indicating that they cannot actively suppress their vocal compensation. In line with these findings, the present study provides further evidence that modulation of vocal compensation for pitch perturbations is independent of whether they are attended or ignored, suggesting that auditory-motor integration in voice control appears to be involuntary at the behavioral level and influenced little by attention.…”
Section: Discussionmentioning
confidence: 65%
“…Typically, vocal compensation for auditory feedback perturbations is exhibited as a corrective response with a short latency approximately ranging from 80–150 ms 5 6 . Behavioral studies have shown that vocally-untrained participants produce vocal compensation for pitch feedback perturbations even when told to ignore them throughout the experiment 14 15 , and they are unable to suppress vocal responses to pitch feedback perturbations irrespective of being told to ignore or compensate for them 13 16 . Therefore, auditory-motor integration in voice control is generally thought to be involuntary in nature and does not appear to be modified by cognitive function such as attention.…”
mentioning
confidence: 99%
“…Since the external signal is independent of the speaker, auditory feedback is evaluated with respect to an external signal or target on a moment-to-moment basis to ensure that they are broadly comparable. A similar mechanism has been proposed to account for the rapid and robust responses speakers exhibit when instructed to alter their pitch to follow the direction of an auditory perturbation (Hain et al, 2000 ; Patel et al, 2014 ).…”
Section: Discussionmentioning
confidence: 85%